A liberação da maconha no contexto das políticas públicas de controle criminal, penitenciárias e de saúde no Brasil - Costa, Carlos Eduardo de Sousa (2022)
This study sought some answers to the questions that pervade the topic of legalizing the use of cannabis in Brazil, from a perspective/delimitation of the impact of the release of marijuana on public policies of criminal control, penitentiaries and health in Brazil. Data were obtained through bibliographic surveys and legal norms on public policies to combat drug trafficking and prevent the use, consumption and abuse of drugs in the country. The analyzes had Law nº 11.343, of August 23, 2006, as a backdrop, which instituted the National System of Public Policies on Drugs, to show the failure of the democratic State of law, as a provider of public security, in the implementation of the policy public control of drugs. It was found from the discussions that, like most Latin American countries, Brazil has not yet managed to establish coalitions of social policies that allow the elaboration of new public policies to control drugs. Thus, the State is not being efficient in controlling drug trafficking, using many resources and with few expressive results, demonstrating the need to adapt this policy. On the other hand, it was found that countries that have implemented legalization or decriminalization policies have achieved satisfactory results. In this sense, the implementation of public control policies for the reduction of risk and for the reintegration of the user into society, in addition to a gradual legalization associated with a control and inspection system, abandoning the focus on punitive and prohibitionist power and a measure that it imposes itself.